Finding brilliance using positive organizational scholarship in healthcare. Issue 6 (21st September 2015) - Dadich, Ann; Fulop, Liz; Ditton, Mary; Campbell, Steven; Curry, Joanne; Eljiz, Kathy; Fitzgerald, Anneke; Hayes, Kathryn J.; Herington, Carmel; Isouard, Godfrey; Karimi, Leila; Smyth, Anne
Abstract : Purpose: – Positive organizational scholarship in healthcare (POSH) suggests that, to promote widespread improvement within health services, focusing on the good, the excellent, and the brilliant is as important as conventional approaches that focus on the negative, the problems, and the failures. POSH offers different opportunities to learn from and build resilient cultures of safety, innovation, and change. It is not separate from tried and tested approaches to health service improvement – but rather, it approaches this improvement differently. The paper aims to discuss these issues. Design/methodology/approach: – POSH, appreciative inquiry (AI) and reflective practice were used to inform an exploratory investigation of what is good, excellent, or brilliant health service management. Findings: – The researchers identified new characteristics of good healthcare and what it might take to have brilliant health service management, elucidated and refined POSH, and identified research opportunities that hold potential value for consumers, practitioners, and policymakers. Research limitations/implications: – The secondary data used in this study offered limited contextual information. Practical implications: – This approach is a platform from which to: identify, investigate, and learn about brilliant health service management; and inform theory and practice. Social implications: – POSH can help to reveal what consumers and practitioners value about health services and how they prefer to engage with these services. Originality/value: – Using POSH, this paper examines what consumers and practitioners value about health services; it also illustrates how brilliance can be theorized into health service management research and practice.